Speciation of North American pygmy shrews (Eulipotyphla: Soricidae) supports spatial but not temporal congruence of diversification among boreal species. (18th November 2019) - Hope, Andrew G; Stephens, Ryan B; Mueller, Sarah D; Tkach, Vasyl V; Demboski, John R
Abstract: Speciation among many animals was rapid through the Pleistocene, impacted by climate and periodic isolation and reconnection. As such, species limits among often morphologically cryptic lineages may remain unresolved despite clear mitogenomic partitioning. Accumulating evidence from phylogeographical studies is revealing congruent regional differentiation of lineages across taxonomic groups that share ecological and evolutionary traits. Here, we analyse multiple DNA loci and morphology to resolve the geography and timeframe associated with evolutionary history of North American pygmy shrews (genus Sorex ). We then assess lineage diversification among three co-distributed shrew complexes using phylogenetic and approximate Bayesian computation approaches to test a hypothesis of spatial congruence but temporal incongruence of species formation on a continental scale. Our results indicate consistency in regional lineage distributions, partial congruence of the sequence of divergence, and strong but not definitive support for temporal incongruence, suggesting that successive glacial cycles initiated the process of diversification repeatedly through the Pleistocene. Our results emphasize a continuing need for greater genomic coverage in comparative phylogeography, with persistent challenges. We recognize distinct eastern ( Sorex hoyi Baird, 1857) and western ( Sorex eximius Osgood, 1901) species of pygmy shrew based on available evidence, but discuss issues with taxonomic designations considering the continuum of speciation throughout the boreal biome.